2018
DOI: 10.1002/chem.201803612
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenols Revisited: Highly Monodispersed Photoluminescent Nanomaterials as Ideal Building Blocks for Supramolecular Chemistry

Abstract: Fullerenols have been known for decades; however, the photoluminescent (PL) properties and applications in supramolecular chemistry of these molecules have not been well addressed. Herein, a strategy has been developed to purify the as-prepared fullerenols, and the photoluminescence and capabilities of these molecules to form supramolecular self-assemblies were systematically studied. It was found that fullerenols show wavelength-dependent emission with an absolute fluorescent quantum yield of approximately 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 69 publications
(53 reference statements)
1
29
0
Order By: Relevance
“…From the high-resolution spectra of C 1s (Figure f), a broad peak was observed that can be divided into three peaks corresponding to signals from the carbons in C 60 , in C–OH and in C–O–, respectively. Compared to pure fullerenol, the C 1s spectrum of the microcapsules locates at lower binding energies, which is presumably caused by mutual interaction between corresponding functional groups and Fe 3+ .…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…From the high-resolution spectra of C 1s (Figure f), a broad peak was observed that can be divided into three peaks corresponding to signals from the carbons in C 60 , in C–OH and in C–O–, respectively. Compared to pure fullerenol, the C 1s spectrum of the microcapsules locates at lower binding energies, which is presumably caused by mutual interaction between corresponding functional groups and Fe 3+ .…”
Section: Resultsmentioning
confidence: 90%
“…We started with an aqueous solution of 2.0 mg mL –1 fullerenol, to which HCl, PS microspheres, and a rusty nail were introduced successively. In our previous work, the formula of the fullerenol has been calculated to be C 60 (OH) 18.2 (ONa) 3.86 ·6.6 H 2 O, which gives a molecular weight of 1297.24. Thus, a concentration of fullerenol ( c f ) of 2.0 mg mL –1 corresponds to 1.54 mmol L –1 fullerenol and 28.06 mmol L –1 hydroxyl group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations